PLGA-hucMSC-Ex Ameliorates Colitis by Reversing Epithelial-mesenchymal Transition - Liu, Ziyue; Yuan, Jintao; Wang, Lan; Din, Muhammad AzharUd; Tian, Yiqing; Mao, Fei (Current Stem Cell Research & Therapy, 2025)
IntroductionHuman umbilical cord mesenchymal stem cell-derived exosomes (hucMSC-Exs) have been found to exhibit therapeutic effects on inflammatory bowel disease (IBD). However, due to the harsh environment of the gastrointestinal tract, exosomes, as a type of biological drug or carrier of bio-active substances, are still delivered by tail vein injection.MethodIn this study, hucMSC-Ex were coated with poly (lactic-co-glycolic acid) (PLGA) polymer to form microparticles, PLGA-hucMSC-Ex, by double emulsion method.ResultsThe oral administration of PLGA-hucMSC-Ex particles alleviated inflammation in the mice model of IBD by reversing IBD-induced epithelial-mesenchymal transition (EMT).ConclusionThis provides an alternative to exploring IBD treatments, with potential clinical application to relieve IBD in patients.
Keywords: hucMSC